Swimming as an Alternative Treatment for Various Health Conditions: Renang sebagai Alternatif Penanganan Berbagai Kondisi Kesehatan - Andhini, Karina Permata; Supriyono (Universitas Muhammadiyah Sidoarjo, 2026)
Background Swimming is widely practiced as a physical activity and has been associated with diverse health-related benefits due to its low mechanical load and full-body movement characteristics. Specific background In recent years, swimming has also been positioned as an alternative treatment option for individuals experiencing various health conditions requiring recovery and rehabilitation. Knowledge gap Nevertheless, prior studies predominantly discuss physical or mental aspects separately, resulting in limited synthesis of swimming as an integrated treatment approach. Aims This study aims to examine swimming as an alternative treatment for various health conditions through a comprehensive literature review encompassing physical, psychological, and social dimensions. Results The findings indicate that swimming supports muscular function, cardiovascular and respiratory capacity, stress regulation, and psychosocial well-being, while remaining adaptable for conditions such as joint disorders, neurological disturbances, asthma, and scoliosis. Novelty This study offers an integrated treatment-oriented perspective that consolidates physical and mental recovery within a single analytical framework. Implications The results support the inclusion of swimming as a structured alternative treatment within health and rehabilitation programs tailored to individual conditions. Highlights Swimming functions as an alternative treatment across multiple health conditions. Water-based movement allows safe adaptation for rehabilitation needs. Physical recovery and mental regulation are addressed simultaneously. KeywordsSwimming Therapy, Alternative Treatment, Health Conditions, Hydrotherapy, Rehabilitation Exercise